Answer:
(7x +6y)(49x^2 -42xy +36y^2)
Explanation:
The factoring of the sum of cubes is a special form:
a³ +b³ = (a +b)(a² -ab +b²)
We recognize the given expression as a sum of cubes, so we can use this pattern to factor it.
Identifying the cubes
From our memory of the cubes of small numbers (or from the cube root function of our calculator), we can identify the terms as ...
343x³ +216y³ = (7x)³ +(6y)³
Application
Our factoring pattern above can be used with ...
Substituting these values, we have ...
343x³ +216y³ = (7x)³ +(6y)³ = (7x +6y)((7x)² -(7x)(6y) +(6y)²)
343x³ +216y³ = (7x +6y)(49x² -42xy +36y²)